Cloud Based Intrusion Detection Conceptual Model for IoT Objects - Aborujilah, Abdulaziz; Nassr, Rasheed Mohammad; Johari, Abdul Rauf Bin (International Journal of Engineering and Technology, 2018)
IoT is a new paradigm that link the physical objects with Internet. Many of vehicles, home appliances, human health and environmental monitoring and other objects are able to be connected to each other through the IoT network. IoT objects have the ability to sense and exchanging data with each other. However, IoT paradigm brings new challenges related to security issues.Â Â  Intrusion Detection Systems (IDS) is widely used to monitor and secure networks. It is very beneficial applying IDS in IoT environment. This paper suggests a conceptual model to integrate IDS with IoT networks. Initial experiments have been conducted to test the possibility of applying SNORT IDS in IoT environment. The results were very encouraging.